Full-length transcriptome, proteomics and metabolite analysis reveal candidate genes involved triterpenoid saponin biosynthesis in Dipsacus asperoides - Pan, Jie; Huang, Chaokang; Yao, Weilin; Niu, Tengfei; Yang, Xiaolin; Wang, Rufeng (Frontiers in Plant Science, 2023)
Dipsacus asperoides is a traditional medicinal herb widely used in inflammation and fracture in Asia. Triterpenoid saponins from D. asperoides are the main composition with pharmacological activity. However, the biosynthesis pathway of triterpenoid saponins has not been completely resolved in D. asperoides. Here, the types and contents of triterpenoid saponins were discovered with different distributions in five tissues (root, leaf, flower, stem, and fibrous root tissue) from D. asperoides by UPLC-Q-TOF-MS analysis. The discrepancy between five tissues in D. asperoides at the transcriptional level was studied by combining single-molecule real-time sequencing and next- generation sequencing. Meanwhile, key genes involved in the biosynthesis of saponin were further verified by proteomics. In MEP and MVA pathways, 48 differentially expressed genes were identified through co-expression analysis of transcriptome and saponin contents, including two isopentenyl pyrophosphate isomerase and two 2,3-oxidosqualene β-amyrin cyclase, etc. In the analysis of WGCNA, 6 cytochrome P450s and 24 UDP- glycosyltransferases related to the biosynthesis of triterpenoid saponins were discovered with high transcriptome expression. This study will provide profound insights to demonstrate essential genes in the biosynthesis pathway of saponins in D. asperoides and support for the biosynthetic of natural active ingredients in the future.